Adsorption of pharmaceuticals from biologically treated municipal wastewater using paper mill sludge-based activated carbon - Silva, Carla Patrícia (2019)
A waste-based alternative activated carbon (AAC) was produced from paper mill sludge under optimized conditions. Aiming its application in tertiary wastewater treatment, AAC was used for the removal of carbamazepine, sulfamethoxazole, and paroxetine from biologically treated municipal wastewater. Kinetic and equilibrium adsorption experiments were run under batch operation conditions. For comparison purposes, they were also performed in ultrapure water and using a high-performance commercial AC (CAC). Adsorption kinetics was fast for the three pharmaceuticals and similar onto AAC and CAC in either wastewater or ultrapure water. However, matrix effects were observed in the equilibrium results, being more remarkable for AAC. These effects were evidenced by Langmuir maximum adsorption capacities (qm, mg g-1): for AAC, the lowest and highest qm were 194 ± 10 (SMX) and 287 ± 9 (PAR), in ultrapure water, and 47 ± 1 (SMX) and 407 ± 14 (PAR), in wastewater, while for CAC, the lowest and highest qm were 118 ± 7 (SMX) and 190 ± 16 (PAR) in ultrapure water and 123 ± 5 (SMX) and 160 ± 7 (CBZ) in wastewater. It was found that the matrix pH played a key role in these differences by controlling the surface electrostatic interactions between pharmaceutical and AC. Overall, it was evidenced the need of adsorption results in real matrices and demonstrated that AAC is a promising option to be implemented in tertiary wastewater treatments for pharmaceuticals' removal. Graphical abstract Production of an alternative activated carbon (AC) comparing favourably with a commercial AC in the removal of neutral and positive pharmaceuticals from wastewater.